I was a teenage slasher - Jones, Stephen Graham, 1972- (Saga Press, 2024)
"1989, Lamesa, Texas. A small west Texas town driven by oil and cotton-and a place where everyone knows everyone else's business. So it goes for Tolly Driver, a good kid with more potential than application, seventeen, and about to be cursed to kill for revenge. Here Stephen Graham Jones explores the Texas he grew up in, the unfairness of being on the outside, through the slasher horror he lives but from the perspective of the killer, Tolly, writing his own autobiography. Find yourself rooting for a killer in this summer teen movie of a novel gone full blood-curdling tragic"--